(untitled) (Research, Society and Development, 2020)
Information on food labels is essential because it aims to provide consumers with adequate guidance on the quality and quantity of nutritional constituents, allowing the selection of a balanced and healthy diet. The objective was to analyze the knowledge of university students regarding food labels and nutritional information. Cross-sectional study, with data collection through the application of a questionnaire, with questions, on food labeling. The same addressed data regarding the identification of university students: gender, education, age, housing, origin, marital status and family income. The data were tabulated in Office Excel 2016 and analyzed using the GraphPad Prism 6 statistical program. It was found that most university students rarely read labels (59%). The language used (47%) and the font size (30.4%) were the main limitations of compression. The shelf life (28%) and price (18%) directly influenced the choice of food by consumers. The most consulted information was the expiration date (22%) and the caloric value (15%). Thus, it was found that students have difficulties in understanding the labeling and usefulness of nutritional information on foods.